Answer:
-4
Step-by-step explanation:
- y = 3(x+5)²-4
- y= 3(x²+10x+25)-4
- y= 3x²+30x+75-4
- y= 3x²+30x+71
Derivate the function
solve the equation y'= 0
- y'= 6x+30
- 6x+30= 0
- 6x= -30
- x = -5
The extrme value of y is reached in -5
y = 3(-5+5)²-4= -4
4/5 x55
=4/5*55/1
=(4*55)/(5*1)
=220/5
=44/1
=44
Upon a slight rearrangement this problem gets a lot simpler to see.
x^3-x+2x^2-2=0 now factor 1st and 2nd pair of terms...
x(x^2-1)+2(x^2-1)=0
(x+2)(x^2-1)=0 now the second factor is a "difference of square" of the form:
(a^2-b^2) which always factors to (a+b)(a-b), in this case:
(x+2)(x+1)(x-1)=0
So g(x) has three real zero when x={-2, -1, 1}
Answer:
D
Step-by-step explanation:
It's one of each or not both tho:)